Calculation of elastic-plastic geometrically nonlinear frames / Tampriųjų ir plastinių geometriškai netiesinių rėmų skaičiavimas - Liudas Liepa (Mokslas: Lietuvos Ateitis, 2012)
The article discusses an algorithm for optimizing and analyzing steel inelastic frame structures evaluating geometrical nonlinearity. The structure is discretized applying bar type finite elements that can be tensioned, compressed or bended. For such elements, the tangent stiffness matrix, using MatLab symbolic calculations, has been developed. A numerical experiment on the steel frame structure has been performed. The elastic response of frame which elements geometry has changed is calculated using Newton-Raphson iterative load control method. The optimal volume of the structure prior to plastic collapse has been obtained. According to load factor, the sequence of the appearance of plastic hinges has been completed.